Facile synthesis of carbon nanodots from ethanol and their application in ferric(iii) ion assay. Issue 29 (7th August 2015) - Miao, Peng; Tang, Yuguo; Han, Kun; Wang, Bidou
<x xml:space="preserve">Abstract</x> A one-pot synthesis approach is used to prepare carbon nanodots by electrochemical carbonization of ethanol under basic conditions. These materials are further applied in the fabrication of a Fe3+ biosensor.